2008
DOI: 10.1117/1.3037340
|View full text |Cite
|
Sign up to set email alerts
|

Flexible miniature compound lens design for high-resolution optical coherence tomography balloon imaging catheter

Abstract: We report on a new optics design for an optical coherence tomography (OCT) balloon imaging catheter. The design involves a miniature compound gradient-index (GRIN) rod lens, which consists of a fiber optic mode-field reducer and relay rod lenses to achieve predictable high lateral resolution at a desired large working distance. The compound lens design significantly simplifies the engineering process for an OCT catheter and enables 3-D full circumferential cross sectional imaging of large luminal organs such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 12 publications
2
45
0
Order By: Relevance
“…One solution to this dilemma was to use a balloon-based centering device ( Figure 6.1A). Balloonbased helical scanning catheters act to dilate the esophagus and to center and stabilize the imaging optics within the lumen [15][16][17]. This is advantageous when the lumen size is large and exceeds the ranging depth of the OCT imaging system.…”
Section: Circumferential Scanning Cathetersmentioning
confidence: 99%
“…One solution to this dilemma was to use a balloon-based centering device ( Figure 6.1A). Balloonbased helical scanning catheters act to dilate the esophagus and to center and stabilize the imaging optics within the lumen [15][16][17]. This is advantageous when the lumen size is large and exceeds the ranging depth of the OCT imaging system.…”
Section: Circumferential Scanning Cathetersmentioning
confidence: 99%
“…10͒. In the future, a spiral-scanning mechanism can be adopted from OCT endoscopy 80 for volumetric imaging.…”
Section: Paementioning
confidence: 99%
“…Circumferential beam scanning was originally implemented with proximal rotary actuation transmitted by a torque cable housing the optical fiber. Later studies demonstrated an optical design using miniature compound gradient-index rod lenses to achieve a small focused spot size (~39 µm, full width at half maximum (FWHM)) at a ~9 mm working distance [7]. In addition, high resolution balloon OCT imaging was achieved by correcting the astigmatism from the plastic sheath with a cylindrical aluminum reflector [8].…”
Section: Introductionmentioning
confidence: 99%